2018
DOI: 10.1001/jamapediatrics.2018.1307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Safety and Efficacy of Methadone vs Morphine for Treatment of Neonatal Abstinence Syndrome

Abstract: IMPORTANCE Although opioids are used to treat neonatal abstinence syndrome (NAS), the best pharmacologic treatment has not been established. OBJECTIVE To compare the safety and efficacy of methadone and morphine in NAS. DESIGN, SETTING, AND PARTICIPANTS In this randomized, double-blind, intention-to-treat trial, term infants from 8 US newborn units whose mothers received buprenorphine, methadone, or opioids for pain control during pregnancy were eligible. A total of 117 infants were randomized to receive metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 27 publications
2
110
0
3
Order By: Relevance
“…Thus, the authors recommended that the choice of medication can affect NAS treatment outcomes, which may have some specificity to the prenatal opioid exposure. The second RCT proposed that short‐term outcomes were better in methadone‐treated infants compared with morphine‐treated infants . In fact, the maternal opioids in this study were buprenorphine, methadone and opioids prescribed for chronic pain.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Thus, the authors recommended that the choice of medication can affect NAS treatment outcomes, which may have some specificity to the prenatal opioid exposure. The second RCT proposed that short‐term outcomes were better in methadone‐treated infants compared with morphine‐treated infants . In fact, the maternal opioids in this study were buprenorphine, methadone and opioids prescribed for chronic pain.…”
Section: Discussionmentioning
confidence: 87%
“…Of the 1020 published studies that were identified, 5 were finally included in this meta‐analysis (two RCTs and three retrospective cohort analyses). Full details of trial selection are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A main concern in this regard is the dramatic escalation in opioid use and abuse together with the resulting increase of babies exposed to opioids during pregnancy and the large percentage of these newborns that are also administered opioids for their treatment of neonatal abstinence syndrome (Stover & Davis, ). We have previously found that the timing of myelination in the rat brain is disturbed by in utero and postnatal exposure to buprenorphine (Sanchez, Bigbee, Fobbs, Robinson, & Sato‐Bigbee, ) and methadone (Vestal‐Laborde, Eschenroeder, Bigbee, Robinson, & Sato‐Bigbee, ), the two opioid analogs currently successfully used in the management of pregnant opioid addicts (Davis et al, ; Kraft et al, ). Our studies suggested a μ‐opioid receptor (MOR) dependent acceleration of myelination induced by therapeutic doses of methadone and buprenorphine.…”
Section: Introductionmentioning
confidence: 99%